ANALISIS VARIABILITAS CURAH HUJAN DAN SUHU PADA HUTAN SEKUNDER PT. MELAPI TIMBER - Susanti Susanti; Prijanto Pamoengkas; Cahyo Wibowo (Universitas Teuku Umar, 2018)
The climate is defined as the condition of mean of air temperature, precipitation, the air pressure, the direction of the wind, air moisture and other parameters in long time. The fluctuations of high rainfall significantly affect plant productivity, such as farming, forestry and agriculture. The amount of rainfall is very important in determine the result of the cultivation of plants. Especially if it is associated with the influence of the increase of temperature. The result of this research showed that the type of land at research location were incepticol (land suitability 1) and ultisol (land suitability II, III, IV and V). The mean of annual rainfall in research location (since 2012 until 2014), were 1500 until 2000 mm/years. The mean air temperature was 26-27 oC and air moisture between 82-85.9 %. Keywords: Melapi Timber, rainfall, temperature, type of land, variability